A STUDY OF THINKING STYLES OF PROSPECTIVE TEACHERS IN RELATION TO THEIR GENDER - Dixit, Ravindra Kumar (International Journal of Research -GRANTHAALAYAH, 2025)
The Present Study assessed the thinking Styles of Prospective Teacher’s in relation to their Gender. The Sample Consisted of 371 Prospective teachers (Male=198, Female=173) who were selected From B.Ed. Colleges of Dr.B.R. A. University, Agra by using accidental technique of sample selection. In the Present study the Normative Survey method of Research was used. Thinking style Inventory Was Constructed by Sternberg & Wagner, as employed for Data collection. Gender is potentially relevant to the development of styles. Male and female Prospective teachers differed significantly in one thinking style only i.e. executive style.Female Prospective teachers tended to be more executive than male prospective teachers in their styles of thinking yon remaining styles no significant between male and Female prospective teachers were observed. These styles were integrated is Legislative, Judicial, monarchic, hierarchic, oligarchic, anarchic global, local, internal, External,Liberal and Conservative.